THE PENAMBAHAN KINESIOTAPING PADA PERLAKUAN MYOFASCIAL RELEASE TECHNIQUE LEBIH BAIK DALAM MENURUNKAN NYERI FUNGSIONALPADA PLANTAR FASCITIS OLEH KARENA PEMAKAIAN SEPATU HAK TINGGI (HIGH HEELS) - Zidni Sadati Maulana Aden; Putu Sutha Nurmawan; Agung Wiwiek Indrayani (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2015)
OBJECTIVE: To determine the influence of kinesiotaping adding for myofascial releasetechnique to decrease the plantar fasciitis functional pain due to the wearing of high hells.SUBJECT: 18 plantar fasciitis subject, devide into two group. Each group consist of 9subject. Group I gets myofascial release technique with kinesiotaping adding and group IIgets only myofascial release technique. RESEARCH PLACE: Physical therapy practice,Sidhi Medika Canggu, Badung.RESEARCH TIME: November – Desember 2014.MEASUREMENT: Pain disability scale/index plantar fasciitis. RESEARCH DESIGN:The research used an experimental method, using to design group pre-test and post-test.RESULT: Each group were tested for normality by the Shapiro wilk test, Group 1 showed pvalue >0,05 and Group II showed p value <0,05. Paired sample t-test for Group I beforeintervention got the mean value 51,88±2,619 and after intervention 27,88±1,364 with p value0,001. Group II were tested with wilcoxon match pair test, the mean value before intervention49,33±4,500 and after intervention 37,88±6,622 with p value 0,007. The result showed thatboth of group happened to decrease morning pain significantly. The next statistical test is thedifference decreased the plantar fasciitis functional pain value with mann whitney u test,mean of Group I 13,56 and Group II 5,44 with p value 0,005, which means there is asignificant difference between Group I and Group II. CONCLUTION: The addition ofkinesiotaping with the myofacial release technique is better than only myofascial releasetechnique to decreasing the plantar fasciitis functional pain due to the wearing of high heels.